ENERGY REQUIREMENTS FOR MAINTENANCE AND EGG PRODUCTION FOR BROILER BREEDER HENS (REQUERIMIENTO DE ENERGIA METABOLIZABLE PARA MANTENIMIENTO, PRODUCCION DE HUEVOS, EN REPRODUCTORAS PESADAS - REYES CORONEL, MARTHA ESTHER (2012)
Feed costs represent around 70% of the poultry production costs. Nutritional requirements for any nutrient needs to be fully understood in order to know the potential risk in production when trying to reduce feed costs and develop appropriate margins of safety. Research in the area of the energy requirements has been focused on estimating the energy requirements for laying hens while for broiler breeder hens the information is slowly being developed. Metabolizable Energy (ME) requirements for broiler breeder hens are higher than for commercial layers primarily because of their larger body size. Nevertheless, in many cases the maintenance energy requirement of metabolizable energy (MEm) has been extrapolated from studies conducted mainly with Leghorn type hens (Leeson, 2003).